A pesquisa etnográfica e sua importância para os estudos de aquisição de língua estrangeira (Revista de Estudos da Linguagem, 1998)
Abstract This article intends to give a general view of the discussions around a scientific method of classroom research called ethnography. This research method came from the social sciences with a clear concern for providing a cultural explanation of social groups. But, within the field of applied linguistics, the tradition of a quantitative view of research brought some other concerns to this research method, such as validity and reliability. However, in relation to the definition and to the essential elements of ethnography there is agreement among all authors.